MENINGKATKAN AKTIVITAS, KETERAMPILAN BERKOMUNIKASI DAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING, NUMBERED HEADS TOGETHER, DAN SCRAMBLE PADA SISWA KELAS 4 DI SDN SUNGAI MIAI 4 BANJARMASIN - Helda Susanti; Mahmuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the 21st century, students are required to master critical thinking, communication, collaboration, and creativity skills, while educators are expected to innovate by applying learning strategies aligned with technological advancements. However, observations in Grade IV at SDN Sungai Miai 4 Banjarmasin revealed that most students remained passive, lacked self-confidence, and faced difficulties in expressing their opinions orally. This study aims to improve students’ learning activity, communication skills, and learning outcomes through the implementation of a combination of Problem-Based Learning (PBL), NHT(NHT), and Scramble models. The research employed Classroom Action Research (CAR) with three cycles, involving 18 fourth-grade students. Data were collected through observations, assessment instruments, and achievement tests, and then analyzed using descriptive qualitative and quantitative methods. The results indicated that teacher engagement increased to the “very good” category, student activeness reached an “almost entirely very high” criterion, and communication skills developed to an “almost entirely very good” level. Furthermore, students’ academic performance achieved both individual and group mastery standards, with 81% obtaining scores ≥70. Therefore, the integration of Problem-Based Learning, Numbered Heads Together, and Scramble models proved effective in creating an active and enjoyable Indonesian language learning environment while contributing positively to the enhancement of students’ competencies.